HUBUNGAN POLIMORFISME GEN ANGIOTENSIN CONVERTING ENZYME DENGAN PERBAIKAN FRAKSI EJEKSI VENTRIKEL KIRI PADA PASIEN GAGAL JANTUNG KRONIK - Handayani, Ahmad; Thristy, Isra; Andina, Meizly (Universitas Muhammadiyah Sumatera Utara, 2021)
Angiotensin-converting enzyme (ACE) is a circulating and membrane-bound enzyme in the renin-angiotensin system. Polymorphism is the presence of two or more alleles at a locus in a population. In patients with heart failure with impaired systolic function, the RAA system is activated. One of the main therapies in heart failure is the administration of angiotensin-converting enzyme blockers. This study aims to examine the relationship between angiotensin-converting enzyme gene polymorphisms with improvement in left ventricular ejection fraction (FEVK).This research is a prospective observational study using a convenient sampling technique, carried out at Mitra Medika Hospital Bandar Klippa, Deli Serdang. The number of samples in the study was 37 people. Each patient was examined for initial echocardiography and at least 1 month after treatment when clinical improvement was seen. All patients received treatment according to the standard guidelines for the management of chronic heart failure according to the European Society of Cardiology (ESC)/Indonesian Cardiovascular Specialist Doctors Association (PERKI). The majority of research subjects were male as much as 81% and the average age of the patients was 56 years. ACE gene polymorphism was dominated by gene II as much as 57%. The average FEVK value in the first measurement was 25.8% and in the second measurement, it increased to 34.4%. There was a significant change between FEVK I measurements by an average of 25% to 34% in the next measurement (p 0.05). In the analysis of the relationship, it was seen that the ACE gene polymorphism did not affect the improvement of the FEVK value.Treatment of chronic heart failure with a decrease in ejection fraction was seen to have a significant effect in increasing FEVK. There is no relationship between angiotensin-converting enzyme gene polymorphisms on response to therapy in patients with chronic heart failure in this study.